ヘンセイ ソリ ノ ソウコウ テイコウ ニ ツイテ - 細谷, 昌之; ホソヤ, マサユキ; 喜納, 淳; キノウ, アツシ; HOSOYA, Masayuki; KINOU, Atsushi (国立極地研究所, 1970)
P(論文) From September 1968 to February 1969, the 9th JARE (Japanese Antarctic Research Expedition) traveled to the South Pole with the aid of snow vehicles and sledges. In order to ensure the mobility of the travel, the tractive effort of the snow vehicles on the crust surface of snow in Antarctica and the running resistance of the composed sledges were tested. The results of the tests revealed that the maximum tractive force of one vehicle on crusted surface in Antarctica is 15.4 tons, the static frictional resistance coefficient μ_s is 0.68, and the dynamic frictional resistance coefficient μ_d is 0.51 at 3 km/h vehicle speed. When the snow vehicle towed five composed sledges, or was loaded with 15.4 tons, behavior of the vehicle was considerably hampered, especially in the motions of turning or crossing a drift of snow. Therefore, 15.4 tons may be a critical value of load. Paying attention to this point, the movement of the traverse party became considerably easy. departmental bulletin paper